Human immunodeficiency virus (HIV)-mediated cardiac fibrosis: implication of cellular immunomodulation and cytokine profile alterations - Mukonowenzou, Nyasha Charity (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.